Cesarean scar pregnancy: an upcoming challenge - Juneja, Sunil K.; Tandon, Pooja; ., Bhanupriya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Cesarean scar pregnancy (CSP) is a type of ectopic pregnancy implanted in the myometrium at the site of previous cesarean scar. Incidence of cesarean deliveries are increasing globally, leading to rise in incidence of cesarean scar pregnancy. Caesarean scar pregnancies are associated with some life-threatening complications such as scar rupture, haemorrhage, disseminated intravascular coagulation, requiring lifesaving hysterectomy. We present our experience with 11 patients with cesarean scar pregnancy, diagnosed using transvaginal colour doppler ultrasound during 3-year period and treated conservatively to preserve the uterus with successful outcome in all patients. Methods: This was a retrospective study, conducted in the Department of Obstetrics and Gynecology of DMC&H, Ludhiana from January 2015 to December 2017. Out of total deliveries (4278), 3.9% (171/4278) were diagnosed as ectopic pregnancy. 6.43% (11/171) of them were diagnosed as cesarean scar ectopic pregnancy. After counseling, all patients underwent conservative management. Injection methotrexate 50mg was administered intramuscularly and beta- HCG was monitored after 4 days and then weekly till it was <1. Results: 2 patients had an increase in beta HCG levels on day 7 and required second dose of methotraxate. 8 patients required blood transfusion due to excessive bleeding on admission. In 9 patients beta HCG levels reduced to <1 in 7 weeks post first methotraxate dose administration, and in remaining 3 it returned to <1 after 8 weeks . No patient required any surgical intervention. Conclusions: Cesarean scar pregnancy, a type of ectopic pregnancy can be safely managed conservatively if diagnosed early.